Surgical Management of Bronchobiliary Fistula After Thoracoabdominal Trauma. Issue 6 (June 2022) - Coughlin, Julia M.; Bonomo, Steven; Chan, Edie Y.; Hasan, Jafar; Grevious, Mark A.; Geissen, Nicole
Bronchobiliary fistulas are exceedingly rare pathological connections between the biliary and the bronchial systems, which result from hepatobiliary neoplasms, abscesses, or thoracoabdominal trauma. Prompt recognition, diagnosis, and intervention is essential in order to prevent the high morbidity and mortality associated with this disease process. Multiple management strategies have been described in the literature; however, the optimal course has not been well defined. We present a case of a 31-year-old male who developed a bronchobiliary fistula 1 month after thoracoabdominal trauma. After conservative management with biliary stenting failed, he successfully underwent latissimus sparing right posterolateral thoracotomy, complete fistulectomy, right lower lobe wedge resection, and diaphragmatic reconstruction with subsequent resolution of his symptoms.